From Mansions to Towers: A History of Residence Halls at the University of Wisconsin-Eau Claire - Skeen, Mitchell A. (My University, 2012)
The construction of the University of Wisconsin-Eau Claire's residence halls has generally followed that of the national trend. The school struggled to find enough funds to build residence halls in the early years. Eventually, student housing was in needed so badly that the school had no choice but to provide housing for the students. In 1947, the Dulany mansion was purchased and remodeled by the school. This building served as the University's first resident hall. Since then, eleven resident halls have been built on campus with one more being planned. Life in these residence halls have changed dramatically over time. In the 1960's, the students protested and eventually the strict rules of in loco parentis faded away. After this, students enjoyed the freedoms of new technologies, relaxed rules, and more professional housing leaders. Today, UW-Eau Claire is a thriving university. UW-Eau Claire has been recognized by many as a top school in the Midwest. Much of the success can be attributed to the residence halls and the happiness of the students. My paper will provide UW-Eau Claire and its students with a cohesive history of the residence halls on campus and will also show how student life has evolved since the University was first established.
Keywords: University of Wisconsin--Eau Claire--Buildings--History; University of Wisconsin--Eau Claire. Housing and Residence Life Office; Dormitories--Wisconsin--Eau Claire--History; College students--Wisconsin--Eau Claire--Conduct of life